Cloning of the prepro c-rfa gene and brain localization of the active peptide in salmo salar - Montefusco-Siegmund, R. A.; Romero, A.; Kausel, G.; Muller, M.; Fujimoto, M.; Figueroa, J. (Cell and Tissue Research, 2017)
12 FONDECYT FONDECYT 325